Síntese de novos heterociclos a partir do ácido levulínico - Piovesan, Luciana Almeida (2009)
The synthesis of new compounds alkyl 3-azolyl propanoate e alkyl 3-azolyl propanoic acid structurally analogues to gamma-aminobutiric acid (GABA) is reported. One more time using the acetal acylation method, now the acetal derivative of 4-oxopentanoic acid (levulinic acid), the methyl 4,4- dimethoxypentanoate, were obtained the precursors methyl 7,7,7-trifluoro[chloro]-4- methoxy-6-oxo-heptenoates, 1,3-dieletrophilic precursor with alcanoate substituent. Are presented efficient and regioespecific synthetic routes from reactions of cyclocondensation [3+2] among 1,3-dieletrofilic precursors with hydroxylamine and different hydrazines, until training isoxazoles and pyrazoles, functionalized with the side chain alkyl propanoate or propanoic acid. Simultaneously to the formation of heterocycles, were studied the hydrolysis reaction of trichloromethyl group and transesterification reaction of methyl propanoate, in the same reactional medium. All products are novel, presenting a good to excellent yields, high purity and the structures were assigned by 1H NMR, 13C NMR and mass spectrometry.